Evaluation of flux trapping moat position on AQFP cell performance. Issue 1 (July 2021) - Fourie, Coenrad J; Takeuchi, Naoki; Jackman, Kyle; Yoshikawa, Nobuyuki
Abstract: With recent advances in InductEx and the TetraHenry numerical engine, it is now possible to analyze the coupling of trapped flux in moats to superconductor circuit structures. Here we show the analysis of moat position in the layout of an adiabatic quantum-flux-parametron (AQFP) buffer cell on the coupling to critical inductors such as the load inductor. This inductor is often carefully laid out to balance current flow and cancel out stray coupling between clock and dc current excitation lines. We investigate the effect of trapped flux that couples asymmetrically to the circuit—either due to the moat position and shape or due to only one of a symmetrical duo of moats being filled with a trapped fluxon—on circuit operating margin and performance. We conclude with suggestions on moat placement to reduce the chances of circuit failure when fluxons are trapped in the moats.